THE EFFECT OF DEBT TO EQUITY RATIO, INVENTORY TURNOVER, AND TOTAL ASSETS TURNOVER ON RETURN ON ASSET: (Study on Chemical Subsector Listed on Indonesia Stock Exchange 2018-2020) - Debriantika Debriantika; Sri Hermuningsih; Gendro Wiyono (AKUNTANSI DEWANTARA, 2022)
This study has purpose to analyze and examine financial ratios in chemical and industrial sub-sector companies listed on the Indonesia Stock Exchange in 2018-2020. The population in this study are chemical and industrial sub-sector companies listed on the Indonesia Stock Exchange in 2018-2020. Sampling using purposive sampling. The results showed that the Inventory Turnover (IT), Total Asset Turnover (TATO) and Debt to Equity Ratio (DER) variables simultaneously had an effect on Return On Assets (ROA).